Application of response surface methodology to study the biological removal of nitrogen from effluent of cattle slaughterhouse in a sequencing batch reactor - Lima,Adriana N. de (2014)
The aim of this study was to evaluate the efficiency of a sequencing batch reactor (SBR) on biological removal of nitrogen from cattle slaughterhouse wastewater by nitrification/denitrification processes. The effects of initial concentration of ammoniacal nitrogen were investigated at 100; 150 and 200 mg L-1 and air flow rate at 0.125; 0.375 and 0.625 L min¹ Lreactor-1 on the nitrogen compounds removal, by a Central Composite Rotational Design (CCRD) configuration. There were variations from 9.2 to 94.9%, 4.0 to 19.6% and 20.8 to 92.0% in the conversion of ammoniacal nitrogen to nitrate and nitrite concentration and removal of total nitrogen, respectively. The increase of air flow rate and decrease of the initial concentration of ammoniacal nitrogen resulted in higher efficiencies of total nitrogen removal, as well as the conversion of ammoniacal nitrogen to nitrate. During the pre-established intervals of this study, the removal and conversion efficiencies of nitrogen compounds above 85% were achieved in air flow rate variations from 0.375 to 0.725 L min-1 Lreactor-1 and initial concentration of ammoniacal nitrogen from 80 to 200 mg L-1. On denitrification process, we obtained efficiencies from 91.5 to 96.9% on the removal of nitrite/nitrate and from 78.3 to 87.9% on the removal of organic matter.